The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.2307/3281974
|View full text |Cite
|
Sign up to set email alerts
|

Capping of Immune Complexes by Sporozoites of Eimeria tenella

Abstract: Sporozoites of Eimeria tenella were incubated for 10, 20, or 30 min with parasite-specific monoclonal IgG antibody 3D3II from mice and then rinsed in a Tris-buffered glucose saline solution (TBGS). Some sporozoites were then incubated for 10, 20, or 30 min with ferritin- or colloidal gold-conjugated goat anti-mouse IgG antibody and then fixed in 2.5% glutaraldehyde and prepared for transmission (TEM) or scanning (SEM) electron microscopy. Other sporozoites that had been previously exposed to monoclonal antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Inhibition may involve specific antibodies in the mucosa of immune birds which act by directly blocking invasion or by enhancing intraluminal destruction of sporozoites. However, E. tenella has been observed capping and shedding immune complexes (Speer et al, 1985b), and sporozoites taken from the caeca of immune birds develop normally when transferred to naive chickens (Rose, 1987). Conversely, E. acervulina immune birds had 11% more intracellular sporozoites (Augustine & Danforth, 1986) than controls, but they do not develop indicating that immunity interferes with further development, not simply invasion.…”
Section: Sporozoite Invasion and Transportmentioning
confidence: 99%
“…Inhibition may involve specific antibodies in the mucosa of immune birds which act by directly blocking invasion or by enhancing intraluminal destruction of sporozoites. However, E. tenella has been observed capping and shedding immune complexes (Speer et al, 1985b), and sporozoites taken from the caeca of immune birds develop normally when transferred to naive chickens (Rose, 1987). Conversely, E. acervulina immune birds had 11% more intracellular sporozoites (Augustine & Danforth, 1986) than controls, but they do not develop indicating that immunity interferes with further development, not simply invasion.…”
Section: Sporozoite Invasion and Transportmentioning
confidence: 99%
“…As suggested by Davis and Porter (1979), antibodies or enzymes within digestive tracts of immune animals may not completely abolish host cell penetration, but may alter parasites rendering them incapable of further development. Speer et al (1985) found that jncubation in a monoclonal antibody alone did not by itself induce capping of immune complexes by E . tenella sporozoites.…”
Section: Methodsmentioning
confidence: 98%
“…Except for the work of Speer et al (1983aSpeer et al ( , 1983Speer et al ( b, 1985 concerning monoclonal antibodies, there have been no previous immunoelectron microscopy (IEM) investigations using imrnunodeterminate site markers on Eimeria species. We report herein the ultrastructural localization of parasite-specific IgA and IgG on Eimeria falciformis oocysts, sporocysts, sporozoites , and merozoites.…”
Section: Introductionmentioning
confidence: 96%
“…It is unclear as to the precise fate of ligands cleared from the surface of sporocysts. Mammalian lymphocytes and fibroblasts predominantly endocytose 'capped' complexes (Raff & de Petris 1973, Bretscher 1984, while most parasitic protozoans shed surface immune complexes (Dzbenski et a1 1976, Schmunis et al 1980, Speer et al 1985. Samuelson, Caulfield & David (1981) documented lateral mobility and shedding of con A-receptor complexes with surface membranes of the schistosomula of S. mansoni and found no evidence for internalization of these complexes.…”
Section: Gar) At 4" C (Con A/anti-con A/r-gar [4"c]) or In The Presementioning
confidence: 99%
“…Ligand-induced modulation of surface membrane determinants is a common event in many motile eucaryoticcell systems. A variety of mammalian cells (Nicholson 1974,1976, Schreiner & Unanue 1976, invertebrate blood phagocytes (Yoshino 1986, Dageforde, Schmucker & Renwrantz 1986, and parasitic protozoa (Speer et al 1985) undergo the sequential processes of 'patching' and 'capping' following binding of specific multivalent ligands to surface receptors. The fluidity of the lipid bilayer plasma membrane permits the aggregation of ligand-linked receptors into island 'patches' that coalesce, usually forming a single 'cap'.…”
Section: Introductionmentioning
confidence: 99%